THE VOICED CONSONANTS’ L AND R PRONUNCIATION CORRECTION OF 5 – 6 YEARS OLD CHILDREN - Upeniece, Jolanta (Education Reform: Education Content Research and Implementation Problems, 2019)
Language development disorders in preschool tend to increase year by year. 5-6 years old children have to acquire a correct pronunciation. It is looked upon a correction of sound L and R pronunciation in a paper. Not pronouncing these sounds makes it difficult to acquire a reading and writing skills, which in time may cause learning and socializing disorders. That is why it is important to obtain a correct pronunciation of all sounds at the age of 5-6 years. The paper’s aim is to analyse the efficiency of methodological material about the voiced consonants L and R automation and differentiation for 5-6 years old children. The obtained data were coded and processed by the SPSS programme.